A Qualitative Study on Parents with Smartphone Addiction Children in Banda Aceh: Phenomenological Approach - Amir Hidayat; Nurjannah; Irwan Saputra; Said Usman; Muhammad Yani (Universitas STRADA Indonesia, 2022)
Background: The need for smartphones in children not only as a communication tool but also as a school learning media so that there is a risk of smartphone addiction. Weak parenting patterns have resulted in many children experiencing smartphone addiction. Purpose: This study aims to explore the experience of role-based parents with smartphone addiction in child. Methods: This study used qualitative design with a phenomenological approach. There were ten participants in this study. The data collection method used in-depth interviews with guidelines that had been prepared based on a theoretical framework and related literature studies. Data collection tools used in this study consisted of interview guidelines and field notes. Results: Based on the results of data collection conducted by researchers, there are four themes that represent the results of the study, parent's role as mentoring, parent's role as modelling, parent's role as organizing and parent's role as teaching. Conclusion: Parents need to provide time and affection for their children so that the diversion of children towards smartphones decreases.